Finding George Freeman: a 'Liberated African' in Berkshire in the Age of Abolition. - Moore, Graham (Slavery & Abolition, 2025)
This article comprises a biography of George Freeman, an African boy 'liberated' from enslavement in West Africa and relocated to the countryside of Berkshire, UK. The article contributes to scholarship on the long-term presence and lived experiences of Black people in Britain, using digital humanities techniques and parochial records from the county of Berkshire to map the presence of Black people (and other minority ethnicities) in rural English counties. It also uses Freeman's biography to engage in wider discussions concerning the precarious experiences of 'Liberated Africans'. These two research areas are combined to construct Freeman's biography as a global microhistory, adding to the growing scholarship that aims to overcome these areas of archival silence within histories of slavery and abolition.